Chapter 21: Indigenous Data Sovereignty - Kukutai, Tahu (The State of Open Data; Histories and horizons, 2019)
Keywords: data; data sovereignty; iwi governance; open data

Reflections on Indigenous sovereignty - Kukutai, Tahu (Journal of Indigenous Wellbeing, 2019)
Keywords: data; data sovereignty; indigenous data sovereignty

Mana motuhake ā-raraunga: datafication and social science research in Aotearoa - Kukutai, Tahu; Cormack, Donna (Kōtuitui: New Zealand Journal of Social Sciences Online, 2019)
Keywords: census; colonisation; data; ethics; statistics

Good data practices for indigenous data sovereignty and governance - Lovett, Raymond; Lee, Vanessa; Kukutai, Tahu; Cormack, Donna; Rainie, Stephanie; Walker, Jennifer (Institute of Network Cultures, 2019)
Indigenous Data Sovereignty (IDS) and Indigenous Data Governance (IDG) art terms increasingly being used across community, research, policy and in practice. The IDS movement has emerged in response to poor data practices, from the conceptualisation of data items through to reporting of data about Indigenous peoples. This chapter aims to provide clarity concerning the definitions of IDS and IDG; provide an overview of the historical context in which IDS has emerged; and provide examples of IDS and IDG across the spectrum of community, policy and practice.
Keywords: data; data sovereignty; statistics